Amplifying the Hawking Signal in BECs - Roberto Balbinot; Alessandro Fabbri (Advances in High Energy Physics)
We consider simple models of Bose-Einstein condensates to study analog pair-creation effects, namely, the Hawking effect from acoustic black holes and the dynamical Casimir effect in rapidly time-dependent backgrounds. We also focus on a proposal by Cornell to amplify the Hawking signal in density-density correlators by reducing the atoms’ interactions shortly before measurements are made.